Heat Transfer of Laminar Mixed Convection of Liquid - Shang, De-Yi; Zhong, Liang-Cai (Heat and Mass Transfer,, 2016)
This book presents a new algorithm to calculate fluid flow and heat transfer of laminar mixed convection. It provides step-by-step tutorial help to learn quickly how to set up the theoretical and numerical models of laminar mixed convection, to consider the variable physical properties of fluids, to obtain the system of numerical solutions, to create a series of formalization equations for the convection heat transfer by using a curve-fitting approach combined with theoretical analysis and derivation. It presents the governing ordinary differential equations of laminar mixed convection, equivalently transformed by an innovative similarity transformation with the description of the related transformation process. A system of numerical calculations of the governing ordinary differential equations is presented for the water laminar mixed convection. A polynomial model is induced for convenient and reliable treatment of variable physical properties of liquids. The developed formalization equations of mixed convection heat transfer coefficient have strong theoretical and practical value for heat transfer applications because they are created based on a better consideration of variable physical properties of fluids, accurate numerical solutions and rigorous formalization equations combined with rigorous theoretical derivation. This book is suitable for scientific researchers, engineers, professors, master and PhD students of fluid mechanics and convection heat and mass transfer.